On reconstruction of complex-valued once differentiable conductivities - Lakshtanov, Evgeny (2016)
The classical ∂-method has been generalized recently ([13] and [14]) to be used in the presence of exceptional points. We apply this generalization to solve Dirac inverse scattering problem with weak assumptions on smoothness of potentials. As a consequence, this provides an effective method of reconstruction of complex-valued one time differentiable conductivities in the inverse impedance tomography problem.